International Negotiations in Multinational Company of IUY. - Kolesnik, Nikolaj (2015)
Negotiation has been a frequent subject of research over past centuries, especially in 20. century this area of business has been recognizing an increasing popularity. This thesis is exploring connections between employees' behaviour of the International Union of Youth in Prague and their negotiation style. Pursuant the research it appears that we can predict employees negotiation style if we are familiar with their behaviour. Moreover, findings showed that there are positive and negative correlations between style of negotiation and behaviour of employees.